2022
DOI: 10.1108/bij-04-2021-0223
|View full text |Cite
|
Sign up to set email alerts
|

Addressing sustainability during and post-COVID-19 pandemic crisis: a literature review and bibliometric analysis to explore the future avenues

Abstract: PurposeThis paper aims to identify the current research trends in sustainability through an extensive literature review and propose future research agenda under the ambit of the ongoing coronavirus disease 2019 (COVID-19) pandemic. Specifically, the present study aims to uncover the current state of the literature and thereby develop an understanding of how the pandemic has impacted the dimensions of sustainability.Design/methodology/approachTo achieve the objective, the authors adopted a five-step literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Organizations with robust GSCMP activities (such as GSCC, green design, and green manufacturing) can achieve superior environmental performance. This aligns with previous research that identified GSCMP activities as a factor in enhancing corporate performance (e.g., Devi & Srivastava, 2022; Habib et al, 2020; Rehman Khan & Yu, 2021). Additionally, this finding supports RBV in explaining the influence of organizational practices (e.g., GSCMP) on firm performance (e.g., environmental performance) and its role in the review of GSCMP in the context of pandemics.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Organizations with robust GSCMP activities (such as GSCC, green design, and green manufacturing) can achieve superior environmental performance. This aligns with previous research that identified GSCMP activities as a factor in enhancing corporate performance (e.g., Devi & Srivastava, 2022; Habib et al, 2020; Rehman Khan & Yu, 2021). Additionally, this finding supports RBV in explaining the influence of organizational practices (e.g., GSCMP) on firm performance (e.g., environmental performance) and its role in the review of GSCMP in the context of pandemics.…”
Section: Resultssupporting
confidence: 91%
“…In the post‐COVID‐19 era, as the global economy and the GSCMP continue to recover, it is essential to conduct more extensive empirical studies on this relationship for the following reasons. First, COVID‐19 has disrupted global supply chains by adversely affecting value chain hubs located in China, the United States, and Europe (Devi & Srivastava, 2022). Second, to manage supply chain disruptions and improve supply chain resilience, manufacturing companies are outsourcing production overseas to avoid future supply bottlenecks (Ivanov, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They implemented environmental accounting principles in healthcare facilities before, during, and after the COVID-19 pandemic, adhering to relevant regulatory requirements regarding cost disclosure and financial report preparation. Devi and Srivastava (2022) found that the pandemic profoundly affected the social, economic, and environmental aspects of sustainability. Nevertheless, during the COVID-19 pandemic, there was a substantial surge in the volume of patients seeking medical attention at hospitals (Priyan, Matahen, Priyanshu, & Mouqdadi, 2024).…”
Section: Discussionmentioning
confidence: 99%